The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0109728
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Rabbit Oct4 Promoter-Based EGFP Reporter System

Abstract: Rabbits are commonly used as laboratory animal models to investigate human diseases and phylogenetic development. However, pluripotent stem cells that contribute to germline transmission have yet to be established in rabbits. The transcription factor Oct4, also known as Pou5f1, is considered essential for the maintenance of the pluripotency of stem cells. Hence, pluripotent cells can be identified by monitoring Oct4 expression using a well-established Oct4 promoter-based reporter system. This study developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Moreover, the information provided here could be used instead of mouse or human sequences to construct vectors for more efficient reprogramming of rabbit somatic cells to pluripotency. In support of this, a POU5F1 promoter from rabbit was found to be more suitable than promoters from different species when a reporter system was constructed (Quan et al, 2014). Implementing the newly identified genes either as biomarkers or as reprogramming factors might eventually lead to the creation of stable rabbit pluripotent cell lines.…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, the information provided here could be used instead of mouse or human sequences to construct vectors for more efficient reprogramming of rabbit somatic cells to pluripotency. In support of this, a POU5F1 promoter from rabbit was found to be more suitable than promoters from different species when a reporter system was constructed (Quan et al, 2014). Implementing the newly identified genes either as biomarkers or as reprogramming factors might eventually lead to the creation of stable rabbit pluripotent cell lines.…”
Section: Resultsmentioning
confidence: 90%
“…piPS-LCs were induced in accordance with a previously described protocol[ 16 ]. Briefly, human Oct4, Sox2, Klf4 and c-Myc were separately cloned into lentiviral vector FUGW (Addgene, 14883), and the constructs FUW-hOct4, FUW-hSox2, FUW-hKlf4 and FUW-hc-Myc were packaged into a virus in 293T cell lines by co-transfecting with auxiliary packaging vectors (psPAX2 and pMD2.G).…”
Section: Methodsmentioning
confidence: 99%
“…A number of transcription factors that have been associated with pluripotency in the mouse, human, and livestock embryos, are also expressed in the rabbit. OCT4 is expressed throughout the whole preimplantation period, from a zygote to an implanting blastocyst at 6 dpc, although the expression level decreases over time, as evidenced by mRNA expression analysis , Kobolak et al, 2009, Mamo et al, 2008, Táncos et al, 2015, immunofluorescent labelling (Canon et al, 2018, Yin et al, 2013, and expression of GFP reporters (Quan et al, 2014, Yin et al, 2013. Recent evidence has shown that the decrease might be related to progressive methylation of the 5' regulatory region of POU5F1 and its gradual repression in the rabbit TE (Canon et al, 2018).…”
Section: Preimplantation Development Of the Rabbit Embryo And Early Lmentioning
confidence: 99%
“…In mice, genetic modifications can be effectively introduced by homologous recombination into ESCs (Bronson and Smithies, 1994), however, germline competent rabbit ESC lines are not yet available. Previously, reporter lines such as Oct4-EGFP have been created by transfection of somatic cells and subsequent somatic cell nuclear transfer (Quan et al, 2014, Yin et al, 2013. Although effective, this method is very time-and labour-consuming.…”
Section: The Rabbit As a Model In Biomedical Studiesmentioning
confidence: 99%